A comprehensive strength testing protocol offers no clinical value in predicting risk of hamstring injury: a prospective cohort study of 413 professional football players. Issue 23 (29th July 2017) - van Dyk, Nicol; Bahr, Roald; Burnett, Angus F; Whiteley, Rod; Bakken, Arnhild; Mosler, Andrea; Farooq, Abdulaziz; Witvrouw, Erik
Abstract : Background: Hamstring injuries remain prevalent across a number of professional sports. In football, the incidence has even increased by 4% per year at the Champions League level over the last decade. The role of muscle strength or strength ratios and their association with risk of hamstring injury remain restricted by small sample sizes and inconclusive results. Purpose: The purpose of this study is to identify risk factors for hamstring injury in professional football players in an adequately powered, prospective cohort study. Using both established (isokinetic) and novel (eccentric hamstring test device) measures of muscle strength, we aimed to investigate the relationship between these strength characteristics over the entire range of motion with risk of hamstring injury. Methods: All teams (n=18) eligible to compete in the premier football league in Qatar underwent a comprehensive strength assessment during their annual periodic health evaluation at Aspetar Orthopaedic and Sports Medicine Hospital in Doha, Qatar. Variables included isokinetic strength, Nordic hamstring exercise strength and dynamic hamstring: quadriceps ratios. Results: Of the 413 players included (68.2% of all league players), 66 suffered a hamstring injury over the two seasons. Only isokinetic quadriceps concentric at 300°/s (adjusted for bodyweight) was associated with risk of hamstring injury when considered categorically. Age, body mass and playing position were also associated with risk of hamstring injury. None of the other 23 strength variables examined were found to be associated with hamstring injury. Conclusion: The clinical value of isolated strength testing is limited, and its use in musculoskeletal screening to predict future hamstring injury is unfounded.